2022
DOI: 10.1001/jamainternmed.2021.8098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep Extension on Objectively Assessed Energy Intake Among Adults With Overweight in Real-life Settings

Abstract: IMPORTANCE Short sleep duration has been recognized as a risk factor for obesity. Whether extending sleep duration may mitigate this risk remains unknown.OBJECTIVE To determine the effects of a sleep extension intervention on objectively assessed energy intake, energy expenditure, and body weight in real-life settings among adults with overweight who habitually curtailed their sleep duration. DESIGN, SETTING, AND PARTICIPANTSThis single-center, randomized clinical trial was conducted from November 1, 2014, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 53 publications
0
39
1
1
Order By: Relevance
“…The underlying pathophysiological mechanisms, including sympathetic activation ( 57 , 58 ), cardiac endocrine and metabolic dysfunction ( 11 , 59 ), increased inflammatory mediators ( 60 ), and endothelial dysfunction ( 61 , 62 ), may be involved in the adverse effects of short sleep duration on cardiovascular health. Recent studies have shown that extended sleep duration can reduce the risk of obesity and improve cardiovascular health, especially in people who have long-term sleep deprivation ( 49 , 63 65 ). A recent meta-analysis provided preliminary evidence supporting that prolonging sleep duration can improve cardiometabolic health ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathophysiological mechanisms, including sympathetic activation ( 57 , 58 ), cardiac endocrine and metabolic dysfunction ( 11 , 59 ), increased inflammatory mediators ( 60 ), and endothelial dysfunction ( 61 , 62 ), may be involved in the adverse effects of short sleep duration on cardiovascular health. Recent studies have shown that extended sleep duration can reduce the risk of obesity and improve cardiovascular health, especially in people who have long-term sleep deprivation ( 49 , 63 65 ). A recent meta-analysis provided preliminary evidence supporting that prolonging sleep duration can improve cardiometabolic health ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…obesity and HbA 1c ), with both long (>8 h) and short (<6 h) sleep durations having negative impacts [ 97 ]. By extending the sleep duration of short sleepers, it is possible to improve insulin sensitivity and reduce energy intake [ 117 , 125 ]. However, ’catch-up’ weekend sleep alone is not enough to reverse the impact of insufficient sleep [ 126 ].…”
Section: Therapeutic Options: Lifestyle and Healthy Behaviour Weight ...mentioning
confidence: 99%
“…These findings align with the observational data and suggest that crosssectional associations between short sleep and higher sugar intake is at least in part attributable to a direct effect of short sleep on consumption of foods high in sugar (34) . Similarly, Tasali et al (35) conducted a parallel 2-arm, 2-week randomised controlled trial in eighty healthy young adults (49 % female) with overweight and reporting sleep < 6•5 h/night; the intervention group receiving personalised sleep hygiene counselling resulted in an increase in sleep duration of 1•2 h per night in the sleep extension group (measured by wrist actigraphy), with no differences in sleep efficiency observed. Again, no dietary advice was provided, but nevertheless energy intake, calculated from changes in body composition and energy expenditure (doubly labelled water), decreased in the sleep extension group by 270 kcal/d relative to the control group, and an inverse correlation between energy intake and sleep duration changes was reported (35) .…”
Section: Sleep Duration and Dietmentioning
confidence: 99%